Transformasi Singa Depok dalam Perayaan Khitanan di Indramayu 1989-2019 - Sugiarti Sugiarti (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
Singa Depok or Kuda Depok which means rocking lion/horse is a typical art of Indramayu, Cirebon, Subang and its surroundings. Originally Singa Depok from Subang known as Sisingaan. The Depok Singa parade is usually held in celebration of circumcision or apostleship. This research aims to present the transformation of Singa Depok from the beginning of its arrival in Indramayu around 1980 to 2019. This research uses the Levi Strauss structuralism approach to reveal various cultural phenomena expressed by the Indramayu community as the owner of culture, including art in culture. The focus of his study reveals the structural changes in Singa Depok which include motion, space, time, background music, make-up, clothing, and audience. Historical research steps, namely heuristics, criticism, interpretation and historiography. The findings of this study indicate that Singa Depok art as a ritual tradition as well as a populist tradition from time to time is dynamic. This is shown by the transformation of the outer and inner structures of Singa Depok's performance from time to time. Early in its appearance it resembled a lion, but in its development it was modified to resemble a bull, giant bird, buroq (winged horse), elephant, or dragon following the current trend. Likewise, the accompanying music always uses dangdut songs that were viral at the time. This change is a form of creativity of the artists in order to attract market interest and maintain the existence of Singa Depok itself.